2015
DOI: 10.1007/s12274-015-0802-2
|View full text |Cite
|
Sign up to set email alerts
|

Strong tunability of cooperative energy transfer in Mn2+-doped (Yb3+, Er3+)/NaYF4 nanocrystals by coupling with silver nanorod array

Abstract: Fluorescent rare-earth ions are useful for efficient energy transfer via multichannels with different properties. Tuning these transfer processes in functional rare-earth materials has attracted considerable attention to satisfy the various demands of diverse practical applications. In this study, strong tunabilities of cooperative energy transfer and nonlinear upconversion emissions are realized using (Yb 3+ , Er 3+ )/NaYF 4 nanocrystals with and without doped Mn 2+ ions by adopting a plasmonic nanocavity com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…As with Yb–Er pairs, energy transfer within Yb–Yb or Er–Er dimers or their clusters is susceptible to surface plasmons . That is also true for energy transfer between lanthanide and transition metals in the presence of metal-cavity-supported surface plasmons . Another exciting work on triply doped β-NaYF 4 :Nd/Yb/Er nanoparticles showed that a rough gold film can generate ultrabroadband plasmons, inducing specific energy transfer between Yb and Er ions, but not between Nd and Yb ions …”
Section: Surface Plasmon–upconversion Couplingmentioning
confidence: 99%
“…As with Yb–Er pairs, energy transfer within Yb–Yb or Er–Er dimers or their clusters is susceptible to surface plasmons . That is also true for energy transfer between lanthanide and transition metals in the presence of metal-cavity-supported surface plasmons . Another exciting work on triply doped β-NaYF 4 :Nd/Yb/Er nanoparticles showed that a rough gold film can generate ultrabroadband plasmons, inducing specific energy transfer between Yb and Er ions, but not between Nd and Yb ions …”
Section: Surface Plasmon–upconversion Couplingmentioning
confidence: 99%
“…UCL was therefore given off either via the aid of or directly from Mn 2+ . [ 13–17 ] In addition, Cr 3+ and Sc 3+ were used in the UC systems to produce novel UCL features. [ 18,19 ]…”
Section: Exploiting Emerging Ucnp Designsmentioning
confidence: 99%
“…The down-shifting process is the conversion of higher-energy photons into lower-energy photons, which often requires two main components, an inorganic matrix (known as the host) and activated Ln 3+ doping ions (activators) [11]. Many types of inorganic compounds, such as oxides, fluorides, phosphates, and vanadates, have been widely used as host materials [12][13][14][15]. Among these materials, fluorides doped with RE ions have low photon energies and high quantum efficiencies, giving them potential for widespread applications in optical communication, display devices, and solid-state lasers.…”
Section: Introductionmentioning
confidence: 99%